TRAINING USE OF PARAMETRIC STATISTICS TO INCREASE MOTIVATION OF FUNCTIONAL EMPLOYEES PLANNING BAPPEDA KLU IN SCIENTIFIC RESEARCH AND PUBLICATION - Dara Puspita Anggraeni (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2021)
This devotion in the form of training aims to increase the motivation of planning functional employees in conducting research and writing scientific articles. The method used is the presentation of parametric statistics followed by completing the case examples using Microsoft Excel, reading and interpreting the output and data processing practices by each participant and ending with filling out questionnaires by the training participants. This training was successful in 83.33% of participants and not successful for 16.67% of participants. The main difficulty for participants in conducting data processing prior to the training was a lack of understanding of the basics of statistical science. (66.67%) followed by the selection of software that was not appropriate (33.33%).